2011
DOI: 10.1002/ijc.25969
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes enhance cell proliferation and LMP1 expression of nasal natural killer/T‐cell lymphoma cells by cell contact‐dependent interaction through membrane‐bound IL‐15

Abstract: Nasal natural killer (NK)/T-cell lymphoma (NNKTL) is an Epstein-Barr virus (EBV)-related malignancy with poor prognosis and has distinct histological features characterized by angiocentric and polymorphous lymphoreticular infiltrates including inflammatory cells such as granulocytes, monocytes, macrophages and lymphocytes. Here, we show that the monocytes enhance proliferation as well as LMP1 expression of NNKTL cells by cell contact-dependent interaction through membranebound interleukin (IL)-15. We used two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 52 publications
0
47
0
Order By: Relevance
“…Intriguingly, we show a strong positive correlation with sCD163 and plasma EBV-DNA levels, suggesting a possible interaction with EBV proteins in HRS cells and CD163 þ monocyte/ macrophages. Monocytes have been shown to enhance proliferation and LMP1 expression of tumor cells in nasal natural killer/T-cell lymphoma (NNKTL), which is also an EBV latency type II-associated malignancy (39). Consistent with this, 4 studies (with sample sizes ranging from approximately 100-300 tissues) have found that tissue CD163 protein does correlate with the presence of EBV-positive HRS cells (13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 82%
“…Intriguingly, we show a strong positive correlation with sCD163 and plasma EBV-DNA levels, suggesting a possible interaction with EBV proteins in HRS cells and CD163 þ monocyte/ macrophages. Monocytes have been shown to enhance proliferation and LMP1 expression of tumor cells in nasal natural killer/T-cell lymphoma (NNKTL), which is also an EBV latency type II-associated malignancy (39). Consistent with this, 4 studies (with sample sizes ranging from approximately 100-300 tissues) have found that tissue CD163 protein does correlate with the presence of EBV-positive HRS cells (13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 82%
“…Our group has demonstrated that monocytes but not granulocytes contribute to NKTL proliferation in a membrane-bound IL-15-dependent manner [21]. Monocytes co-localized with lymphoma cells in NKTL clinical samples.…”
Section: Monocytes and Macrophagesmentioning
confidence: 90%
“…We have previously shown that SNK6 cells produce several cytokines and chemokines such as interferon (IFN)-γ, interleukin (IL)-9, IL-10 and interferon-γ-inducible protein (IP)-10, which play roles in cellular proliferation and invasion in an autocrine manner [7][8][9]. Furthermore, monocytes attracted by IP-10 enhance the proliferation via cell-to-cell contact [10]. However, the biological characteristics of NNKTL are yet to be completely understood.…”
Section: Introductionmentioning
confidence: 99%